EL VOTO NO DEPENDE DE LA COYUNTURA - Jarpa, Paula (La Sociología en sus Escenarios, 2009)
Abstract. The specialist in electoral soundings Miguel Aigneren of the Training center of Opinion of the University of Antioch assures that the Colombians, in spite of all the changes that our society has experienced, we continued voting of way similar to how we did it in the past. Resumen. El especialista en sondeos electorales Miguel Aigneren del Centro de Estudios de Opinión de la Universidad de Antioquia asegura que los colombianos, pese a todos los cambios que ha experimentado nuestra sociedad, seguimos votando de manera similar a cómo lo hacíamos en el pasado